Perceptions of medical students towards antibiotic prescribing for upper respiratory tract infections in Saudi Arabia. Issue 1 (23rd June 2015) - Harakeh, Steve; Almatrafi, Musab; Ungapen, Haifa; Hammad, Rotana; Olayan, Feras; Hakim, Reema; Ayoub, Mohammed; Bakhsh, Noura; Almasaudi, Saad B; Barbour, Elie; Bahijri, Suhad; Azhar, Esam; et al.
Abstract : Introduction: This survey evaluates knowledge, attitudes and practices of medical students towards use of antibiotics for upper respiratory infections (URTIs). Methodology: Cross-sectional questionnaire study among 1042 randomly selected medical students in Saudi Arabia. Results: Respondents were mostly Saudis (97.5%), had previous knowledge of antibiotics (99.7%) and their usage (98.3%) against bacterial infections (93.7%). 18.1% thought that they could be used for viral infections. Nearly all students (97.2%) used antibiotics themselves during the previous year and self-medication without a prescription was high at 49% of cases. Most antibiotics were taken for URTI symptoms (61.8%). Female medical students had better knowledge on antibiotic effectiveness against bacteria and viruses, and overall knowledge increased with study year. Health seeking behaviour rates for symptoms of RTI and associated estimated necessity for antibiotics varied but were highest for cough with yellow/green phlegm. Conclusions: The depth of knowledge that healthcare professionals have in relation to the proper use of antibiotics is essential in spreading the right message within communities. This is the first large study among medical students in Saudi Arabia, shedding important light on areas for improvement in the medical curriculum as well as antibiotic practices of medical students themselves.